Evaluation of an innovative radiographic technique - parallel profile radiography - to determine the dimensions of dentogingival unit - Sushama R Galgali; Gauri Gontiya (Wolters Kluwer Medknow Publications, 2011)
Background: Maintenance of gingival health is a key factor for longevity of the teeth as well as of restorations. The physiologic dentogingival unit (DGU), which is composed of the epithelial and connective tissue attachments of the gingiva, functions as a barrier against microbial entry into the periodontium. Invasion of this space triggers inflammation and causes periodontal destruction. Despite the clinical relevance of the determination of the length and width of the DGU, there is no standardized technique. The length of the DGU can be either determined by histologic preparations or by transgingival probing. Although width can also be assessed by transgingival probing or with an ultrasound device, they are either invasive or expensive Aims: This study sought to evaluate an innovative radiographic exploration technique - parallel profile radiography - for measuring the dimensions of the DGU on the labial surfaces of anterior teeth. Materials and Methods: Two radiographs were made using the long-cone parallel technique in ten individuals, one in frontal projection, while the second radiograph was a parallel profile radiograph obtained from a lateral position. The length and width of the DGU was measured using computer software. Transgingival probing (trans-sulcular) was done for these same patients and length of the DGU was measured. The values obtained by the two methods were compared. Pearson product correlation coefficient was calculated to examine the agreement between the values obtained by PPRx and transgingival probing. Results: The mean biologic width by the parallel profile radiography (PPRx) technique was 1.72 mm (range 0.94-2.11 mm), while the mean thickness of the gingiva was 1.38 mm (range 0.92-1.77 mm). The mean biologic width by trans-gingival probing was 1.6 mm (range 0.8-2.2mm). Pearson product correlation coefficient (r) for the above values was 0.914; thus, a high degree of agreement exists between the PPRx and TGP techniques. Conclusions: We conclude that the biologic width of the DGU in humans can be measured with the PPRx technique. The values obtained agree with the values obtained by transgingival probing, a technique considered standard so far. Thus, the PPRx technique offers a simple, concise, noninvasive, and reproducible method that can be used in the clinical setup to measure both the length and thickness of the DGU with accuracy.